2014
DOI: 10.1155/2014/805929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Different Aspects of Prospective Memory in Amnestic and Nonamnestic Mild Cognitive Impairment

Abstract: Prospective memory, the inability to remember an intended action, is a common complaint, but not formally assessed in most clinical and research studies of mild cognitive impairment (MCI). In this study, patients with amnestic mild cognitive impairment (aMCI), non-amnestic cognitive impairment (naMCI), and cognitively normal (CN) elders were assessed using the Miami Prospective Memory Test (MPMT). A unique aspect of the paradigm was that participants were scored for intention to perform, accuracy in recollecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…One might suppose that aMCI individuals in Delprado et al's study 30 mostly included single-domain aMCI individuals considering their PM deficits were more from difficulties on the RC. Despite these differences, our results are in line with previous findings that aMCI subjects exhibit greater PM deficits relative to naMCI and OA subjects 23,27 and that deficits in naMCI subjects were intermediate between OA and aMCI. 28 Research on PM is increasing in AD and MCI populations because functional and anatomical brain areas known to be impaired in these conditions parallel those involved in PM functioning.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One might suppose that aMCI individuals in Delprado et al's study 30 mostly included single-domain aMCI individuals considering their PM deficits were more from difficulties on the RC. Despite these differences, our results are in line with previous findings that aMCI subjects exhibit greater PM deficits relative to naMCI and OA subjects 23,27 and that deficits in naMCI subjects were intermediate between OA and aMCI. 28 Research on PM is increasing in AD and MCI populations because functional and anatomical brain areas known to be impaired in these conditions parallel those involved in PM functioning.…”
Section: Discussionsupporting
confidence: 92%
“…[20][21][22] Significant PM deficits have also been reported in individuals with mild cognitive impairment (MCI), an intermediate state between normal cognitive functioning and dementia. 19,[23][24][25][26][27][28] Given its essential role in maintaining independent daily living, it would be wise to evaluate PM at a more systematic rate, especially in the aging population. Several standardized PM measures have been developed over the years.…”
mentioning
confidence: 99%
“…However, there are issues concerning the assessment of PM. First, although there are measures that have undergone validation studies and have been shown to be distinct from some unrelated concepts, measures of PM considered valid remain correlated with other measures of "higher" cognition such as working memory (Hernandez Cardenache et al, 2014;Kamat et al, 2014;Salthouse et al, 2004). While this would be theoretically expected to some extent, this raises the question whether we are measuring prospective memory specifically or simply executive function in general.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Importantly, PM deficits may appear early in the neurodegenerative process, namely in patients that suffer from Mild Cognitive Impairment (MCI). [7][8][9][10][11][12] Beyond the actual performance in PM objective tasks, it is also important to consider the subject's self-report about PM complaints. 6 Several studies showed that patients with MCI have objective deficits in PM, using different memory tasks.…”
mentioning
confidence: 99%
“…6 Several studies showed that patients with MCI have objective deficits in PM, using different memory tasks. [7][8][9][10][11][12] Beyond the actual performance in PM objective tasks, it is also important to consider the subject's self-report about PM complaints. The Prospective and Retrospective Memory Questionnaire (PRMQ) 13 is probably the most widely used instrument to evaluate PM.…”
mentioning
confidence: 99%